Identifying State Resources and Support Programs on E-Government Websites for Persons with Intellectual and Developmental Disabilities - Kathleen M. Fisher; Justin D. Peterson; Jon D. Albert (Nursing Research and Practice)
This descriptive cross-sectional study identified resources and programs that are available nationwide on the Internet to support individuals and families with intellectual and developmental disabilities (I/DD), with a focus on intellectual disability. This evaluation included easily identifiable information on specific resources and highlighted unique programs found in individual states that were linked from e-government websites. Researchers documented the ease of access and available information for all 50 states and the District of Columbia. A number of disparities and areas for improvement were recorded for states and I/DD websites. The researchers conclude that a number of additional health and support services will be needed to address the growing needs of this vulnerable population.